The Influence of Transformational Leadership Style, Work Motivation, and Affective Commitment on the Performance of the Tirta Lestari Regional Water Company in the Tuban District, through Employee Performance as a Moderating Variable - Irwanto, Mokh.; Sriyono; Supardi (Jurnal Manajemen (Edisi Elektronik), 2025)
Perusahaan Umum Daerah Air Minum Tirta Lestari a Regional-Owned Enterprise tasked with providing clean water to the com-munity of Tuban Regency, has experienced performance stagnation over the past five years (2019-2023), although overall its performance is still considered good. This study aims to determine the influence of transformational leadership style, work motivation, and affective commitment of employees on the performance of the Regional Drinking Water Company Tirta Lestari in Tuban Regency. This research is a causal study aimed at exploring the influence of independent variables on dependent variables and their impact on the performance of the Regional Drinking Water Com-pany Tirta Lestari in Tuban Regency. Data analysis techniques used include validity testing, reliability testing, and hypothesis testing using a saturated sample of all 114 employees of the company